Dramaturgia "Dwóch ludzi z szafą" - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The Dramaturgy of Roman Polański’s Two Men with a Wardrobe Marek Hendrykowski’s case study on Polański’s famous student etude Two Men with a Wardrobe reconstructs this wonderful short movie take-by-take: a must for anyone who cares about cinema as art. The young (24 years old) director, together with a team of talented colleagues (cameraman Maciej Kijowski, actors Jakub Goldberg and Henryk Kluba, director’s assistant Andrzej Kostenko and film music composer and jazzman Krzysztof Komeda), demonstrated a very modern way of thinking about the art of the moving image and about the various possibilities hidden in the simple poetics of screen drama. From its opening scene on the beach to the dramatic and nostalgic ending with a comeback to the sea, the film charts two men’s struggles on the difficult path to becoming independent human beings enjoying their own freedom.